2011
DOI: 10.1007/s00134-011-2148-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of terlipressin bolus infusion on sublingual microcirculatory blood flow during septic shock

Abstract: In fluid-resuscitated patients with septic shock (with a MAP between 65 and 75 mmHg), a bolus infusion of 0.5 mg terlipressin was effective in reducing NE requirements without worsening microcirculatory blood flow. Randomized clinical trials are now warranted to verify these preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
(56 reference statements)
1
11
0
1
Order By: Relevance
“…In harmony with the effects on the microcirculation, and in line with previous experimental and clinical studies [ 17 - 19 , 23 ], we did not notice differences in arterial pH or in lactate concentrations following TP or AVP administration, suggesting a lack of drug-related impairment of cellular oxygenation as well as the absence of differences in resuscitation quality between groups. In this context, it is also important to note that the multicenter VASST study [ 16 ] demonstrated no differences between AVP and sole NE in the rate of overall adverse events.…”
Section: Discussionsupporting
confidence: 92%
“…In harmony with the effects on the microcirculation, and in line with previous experimental and clinical studies [ 17 - 19 , 23 ], we did not notice differences in arterial pH or in lactate concentrations following TP or AVP administration, suggesting a lack of drug-related impairment of cellular oxygenation as well as the absence of differences in resuscitation quality between groups. In this context, it is also important to note that the multicenter VASST study [ 16 ] demonstrated no differences between AVP and sole NE in the rate of overall adverse events.…”
Section: Discussionsupporting
confidence: 92%
“…Persistent microvascular alterations were associated with organ failure and worse outcome . The microvascular effects of several therapies have been evaluated . Sidestream dark field technology was recently found to have other potential applications, such as in plastic surgery, dermatology and oncology …”
Section: Resultsmentioning
confidence: 99%
“…14,16 The microvascular effects of several therapies have been evaluated. [17][18][19][20][21][22] Sidestream dark field technology was recently found to have other potential applications, such as in plastic surgery, 23 dermatology 24 and oncology. 25 Several microvascular beds (intestine, 26 liver, 27 skeletal muscle, 28 brain 29 ) have been explored in disparate animal models.…”
Section: Resultsmentioning
confidence: 99%
“…Il est à noter que les mesures et l'administration des vasoconstricteurs étaient débutées en médiane 36 heures (entre 21 et 52 heures) après le début du choc septique, sachant qu'il existe peut-être un bénéfice à une administration plus précoce, notamment dans les 24 premières heures, où les altérations microcirculatoires sont les plus sévères. Cette hypothèse est supportée par une autre étude de la même année, de la même équipe, qui montrait que l'injection de terlipressine 0,5 mg en bolus, 28 heures après le début du choc septique avec dépendance à la noradrénaline, améliore la microcirculation (MFI, proportion de capillaires perfusés, index d'hétérogénéité) à h6 de l'injection [61]. En revanche, la méthodologie de cette dernière étude était beaucoup moins pertinente (étude interventionnelle, en ouvert, moins de patients).…”
Section: Effets De La Vasopressine Sur La Microcirculation Chez L'animalunclassified